EVALUASI LAYANAN ONLINE DAN AKSES KE KOLEKSI DIGITAL PERPUSTAKAAN UNIVERSITAS INDONESIA - Kalarensi Naibaho (Perpustakaan Nasional RI, 2020)
In digital era, the University of Indonesia's Library collection is dominated by e-resources (64%). To accommodate these changes, the service concept must also be adjusted. The UI library provides online services where users can interact directly with the library through the system provided. This service has been running for almost 10 years, and needs to be evaluated through studies. This study aims to determine the opinion of users about online services and about access to digital collections of the UI Library. The method used in this study is a survey method (online and direct), while data processing uses SPSS version 17. The number of questionnaires distributed directly is 1000 copies, and the return number is 690 copies, while the number of questionnaires obtained from online is 637 questionnaire, so the total to 1327 questionnaires. After validation, the number of valid questionnaires is: 1061 copies. Sampling is done by nonprobability sampling. The results showed that: the majority of respondents (over 60%) were not aware of the existence of an online library UI service; over 60% have not used the UI Library online service; the UI Library website is quite informative; UI user friendly website interface; the respondent understands the menus on the website. As for access to digital collections: digital collections in the UI Library really help users access collections without having to go to the library; respondents understand how to access the UI library digital collection, but have problems in terms of ease of access; access to digital collections from the UI Library outside the UI network (remote) is very helpful, but often has problems (not accessible); The UI library's online journal collection is very helpful, but it becomes less satisfying when many online journals are accessed because the extension process has not yet been completed.